1998
DOI: 10.1152/jn.1998.79.4.2119
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of Primary Somatosensory Cortex Paralleling Sensorimotor Skill Recovery From Stroke in Adult Monkeys

Abstract: Adult owl and squirrel monkeys were trained to master a small-object retrieval sensorimotor skill. Behavioral observations along with positive changes in the cortical area 3b representations of specific skin surfaces implicated specific glabrous finger inputs as important contributors to skill acquisition. The area 3b zones over which behaviorally important surfaces were represented were destroyed by microlesions, which resulted in a degradation of movements that had been developed in the earlier skill acquisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
204
1
9

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(226 citation statements)
references
References 107 publications
12
204
1
9
Order By: Relevance
“…This is consistent with the neurophysiological findings of animal research reviewed in the introduction indicating that the remodeling of somatosensory neural substrates subsequent to focal cortical lesions generally preserves the original neural topography. In addition, the results from AKH indicating overlapping representational surfaces for ventral digits 4 and 5 and dorsal digits 3 and 4 are consistent with the multi-digit receptive fields that have been observed subsequent to cortical lesions in animals [20]. Finally, the similarity between the results obtained for the dorsal and ventral surfaces constitutes an important contribution to the scarce literature (from either human or animal studies) regarding the plasticity of the dorsal (hairy surface) of the hands.…”
Section: Discussionsupporting
confidence: 80%
“…This is consistent with the neurophysiological findings of animal research reviewed in the introduction indicating that the remodeling of somatosensory neural substrates subsequent to focal cortical lesions generally preserves the original neural topography. In addition, the results from AKH indicating overlapping representational surfaces for ventral digits 4 and 5 and dorsal digits 3 and 4 are consistent with the multi-digit receptive fields that have been observed subsequent to cortical lesions in animals [20]. Finally, the similarity between the results obtained for the dorsal and ventral surfaces constitutes an important contribution to the scarce literature (from either human or animal studies) regarding the plasticity of the dorsal (hairy surface) of the hands.…”
Section: Discussionsupporting
confidence: 80%
“…A previous human study of epilepsy surgery in extratemporal lobe epilepsy suggested that surgical resection of the postcentral gyrus resulted in more pronounced deficits of the contralateral extremities compared to that after resection of the precentral gyrus (Polkey, 2000). Weakness of the contralateral hand associated with lesioning of the postcentral gyrus was attributed to loss of proprioception by the investigators (Polkey, 2000;Xerri et al, 1998).…”
Section: Evidence From Lesion Studiesmentioning
confidence: 98%
“…Previous studies revealed that a lesion (Xerri et al, 1998) or cooling (Brinkman et al, 1985) confined to the presumed postcentral gyrus resulted in hemiparesis of the contralateral upper extremity in monkeys. A previous human study of epilepsy surgery in extratemporal lobe epilepsy suggested that surgical resection of the postcentral gyrus resulted in more pronounced deficits of the contralateral extremities compared to that after resection of the precentral gyrus (Polkey, 2000).…”
Section: Evidence From Lesion Studiesmentioning
confidence: 99%
“…Regarding the spatial aspects of stroke-induced rewiring, studies of brain structure indicate heightened plasticity in periinfarct cortex, with enhanced axonal sprouting, synaptogenesis, and turnover of dendritic spines (Stroemer et al, 1995;Xerri et al, 1998;Cramer and Chopp, 2000;Biernaskie and Corbett, 2001;Carmichael et al, 2001;Carmichael, 2003Carmichael, , 2006Gonzalez and Kolb, 2003;Brown et al, 2007). Interestingly, dendritic spine plasticity is greatest within Ïœ1 mm of the infarct (Brown et al, 2007), indicating the need to evaluate both the function and spatial location of individual neurons in close proximity to the periinfarct cortex.…”
Section: Introductionmentioning
confidence: 99%